2019
DOI: 10.1590/1806-93042019000300013
|View full text |Cite
|
Sign up to set email alerts
|

Association between job satisfaction and workers' quality of life in a public maternity hospital in the far north of Brazil

Abstract: Objectives: to correlate the levels of job satisfaction (JS) and quality of life (QOL) of public maternity workers. Methods: quantitative and correlational cross-sectional study. Sample composed of 199 state public servants, of both genders, of different age groups and professions, working at the Women's Hospital Mother Luzia (WHML), in Macapá (AP). Three questionnaires were used: Sociodemographic, Job Satisfaction S20/23 and WHOQOL-Brief. Statistical analysis was performed by Pearson correlation and analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…[34], and in Brazilian health workers in general, which was 2.55 pts. [35]. These ndings suggest that work in primary health care services is correlated with lower levels of job satisfaction relative to secondary health care services.…”
Section: Discussionmentioning
confidence: 79%
“…[34], and in Brazilian health workers in general, which was 2.55 pts. [35]. These ndings suggest that work in primary health care services is correlated with lower levels of job satisfaction relative to secondary health care services.…”
Section: Discussionmentioning
confidence: 79%
“…In another study, the quality of job life and job satisfaction levels of the nurses were strongly correlated with one another (Baysal & Yildiz, 2019). In their study, Marques‐Duarte and Pureza (2019) found a positive significant correlation between the job satisfaction levels and quality of life of hospital staff members. In their study, Ioannou et al (2015) determined that the nurses who had high levels of job satisfaction had better health‐related quality of life even if they were not satisfied with their job.…”
Section: Discussionmentioning
confidence: 93%
“…Job dissatisfaction usually occurs at the individual, collective, and organizational levels in case of vulgarism problems (Javanmardnejad et al, 2021). Marques‐Duarte and Pureza (2019) found that the overall job satisfaction mean score of the hospital employees was low; Ioannou et al (2015) determined the job satisfaction total mean score of nurses was low (Ioannou et al, 2015). Factors such as harsh working circumstances, irregular working hours, low wage, and a poor professional reputation have been associated with reduced job satisfaction in the nursing profession (Çelik & Kılıç, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A relação entre os perfis de satisfação no trabalho e a qualidade de vida dos docentes evidenciou avaliação homogênea nos domínios da qualidade de vida, demonstrando que esta não se caracterizou como uma variável associada aos índices de satisfação no trabalho. Em outro contexto laboral, pesquisadores constataram que quanto maior a satisfação no trabalho de servidores de uma maternidade pública melhor a avaliação da qualidade de vida (Marques-Duarte & Pureza, 2019).…”
Section: Clusters Punclassified